Exploring nursing culture through sociological and symbolic theoretical approach of organizational culture - Gabriel, E.; Merkouris, Anastasios (My University, 2015)
INTRODUCTION: Organizational culture is the shared beliefs by members of an organization which influence their attitude and behavior. AIM: To explore the nursing culture through the social and symbolic theoretical approaches of organizational culture. METHODOLOGY: Review of the literature in the electronic databases PubMed, CINAHL and Google Scholar without chronological limitations using the keywords: Organizational Culture, Nursing, Leaders, Symbols, Rituals and Values. RESULTS: According to the social approach, nursing culture is influenced by the early history of the profession and particularly from pioneering founders like Nightingale. Nursing culture is associated with perceptions and stereotypes within the broader social context of gender and the female role, and is also influenced by the dominance of medical knowledge. The process of nursing culture growth and integration has been socialization through education and leadership standards. At the same time, beliefs and values of nursing culture are reflected in practices relating to clothing, figures of speech and rituals, which are powerful forms of symbol. These help in complying with professional requirements, in the stabilization of identity and the communication of organizational values both to the organization’s members and to non-members. CONCLUSION: Exploring nursing culture from both theoretical approaches, facilitates the understanding of aspects of values and beliefs that are established and are used as guides in daily nursing practice. However, the nursing culture today must be shaped according to the modern concepts in the provision of healthcare.
Keywords: Leaders; Nursing; Organizational culture; Rituals; Symbols; Values